Mechanisms of chaos in postmodern arts (Pop Art - graphite art is an example) (Al-Academy, 2026)
The current research is concerned with the topic of chaos and its mechanisms in post-modern arts, specifically (Pop Art and Graffiti Art). The research specializes in studying the mechanisms of chaos in post-modern arts, taking Pop Art and Graffiti Art as a model. The importance of the research is evident in shedding light on an important area in the arts. Postmodernism shows methods of rebellion and chaos and how to address them in postmodern arts. The research contained four chapters, and the first chapter included (the methodological framework of the research) and included the research problem and its questions: What is the intellectual content of the mechanisms of chaos that have been absorbed by postmodern arts? To what extent are these aspects reflected in the products of art education students? The aim of the research is to uncover the mechanisms of chaos in post-modern arts (Pop Art - Graffiti Art) in the productions of art education students, while the limits of the research were limited to the following: Some post-modern art schools (popular art, graffiti art) (drawing). The second chapter contained two sections: the first: the mechanisms of chaos in postmodern arts, and the second: some schools that contained chaos in postmodern arts. The third chapter dealt with the applied framework of the research, as it included the research community and selected a purposive sample consisting of (3) samples and then analyzed it according to the descriptive approach in the analytical method. While the fourth chapter included the research results, as well as conclusions, recommendations, and proposals. The research concluded with the most important sources and references.Keywords: chaos mechanisms, postmodern arts, mechanisms, chaos, drawing, plastic arts.